A meta-evaluative synthesis of the effects of custodial and community-based offender rehabilitation - Koehler, Johann A. (European journal of criminology, 2025)
We synthesize 53 meta-analyses on the effectiveness of correctional treatment applied to a wide variety of offender groups delivered in either custodial or community-based settings. Those meta-analyses revealed positive overall effects on reoffending of correctional treatment delivered in both settings. However, the treatment setting is also associated with complex moderator effects. With respect to effect size, for most groups, community-based correctional treatment is associated with statistically significant larger reductions in reoffending than treatments delivered in custodial settings. With respect to effect precision, custodial treatments report more consistent effects on reoffending than community-based treatments. The findings extend and develop the insight that treatment flexibility, such as is found among community-based treatments, can optimize program effectiveness. Likewise, the opportunities for monitoring and treatment fidelity that custodial settings enable can homogenize outcomes. Nonetheless, the promising results observed among treatments delivered both inside and outside institutional settings implicate a complex policy tradeoff between prioritizing strong performance and consistent effects.